Odontogenic Keratocyst Mimicking Paradental Cyst - Andrea Enrico Borgonovo; Luigi Bernardini; Paola Francinetti; Federica Rizza; Dino Re (Case Reports in Dentistry)
Objective. The aim of this paper is to present an uncommon clinical and radiographic aspect of odontogenic keratocyst (OKC) mimicking paradental cyst. Methods. A 32-year-old female patient showed a well-delimited radiolucent lesion connected with the root of the left third molar with close anatomical relationship with the mandibular canal. The clinical, radiographic, and anamnestic features lead us to diagnose a paradental cyst that was treated by enucleation after extraction of the partially impacted tooth. Results. Histological analysis showed typical histological features of PKC such as the presence of a lining of stratified squamous epithelium with a well-defined basal layer of palisading columnar of cuboidal cells. Conclusion. Initial X-ray analysis and the position of the lesion related to the third mandibular tooth caused us to mistakenly diagnose a paradental cyst. We were only able to identify the cyst as an PKC rather than a paradental cyst after histological analysis.